Skeletal muscle in hypoxia: The role of erythropoietin - Hagstroem, L.; Favret, F.; Beaudry, M.; Richalet, J. P.; Launay, T. (High Altitude Medicine & Biology, 2006)
The exact role of erythropoietin (EPO) in skeletal muscles has been little studied and remains unclear. Nevertheless, EPO is supposed to be involved in skeletal muscle development and repair. Moreover chronic hypoxia induces alterations in metabolism and muscular structure. The aim of the study was to determine if EPO is a growth factor essential to maintain muscular typology or if there are factors of compensation such as vascular endothelial growth factor (VEGF). We have studied the muscular adaptations of transgenic mice under-expressing EPO (Epo-Tagh), and thus, severely anemic, in normoxia, acute hypoxia (HxA) and chronical hypoxia (HxC) conditions. Wild type mice (WT) and Epo-Tagh mice have been settled in a hypobaric chamber for 24 hours (HxA) or 14 days (HxC). Soleus and gastrocnemius muscles were removed and analyzed using histological methodes. Typology determination has been carried out by ATPase technique. The amount of VEGF in gastrocnemius has been determined by ELISA. The results of this study show that anaemia, as well as hypoxia, do not modify soleus typology. Histological analyses of Epo-Tagh mouse soleus indicate that chronical hypoxia combined to anaemia may cause degenerescence of muscle fibers. It suggests that EPO is an important factor for muscular structure maintenance in this extreme environment. No consistent difference in the level of VEGF were found between control and anemic mice in normoxia or acute hypoxia. In chronic hypoxic condition, WT mice show a lower concentration of VEGF than Epo-Tagh mice (p < 0.05). Thus, on the one hand there is no compensation to the reduced expression of EPO in HxA while on the other hand there is an evident compensation in HxC, probably due to the muscle regeneration.